2022
DOI: 10.3390/mps5030035
|View full text |Cite
|
Sign up to set email alerts
|

Reference Gene Validation for RT–qPCR in PBMCs from Asthmatic Patients with or without Obesity

Abstract: Obesity is known to impair the efficacy of glucocorticoid medications for asthma control. Glucocorticoid-induced gene expression studies may be useful to discriminate those obese asthmatic patients who present a poor response to glucocorticoids. The expression of genes of interest is normalized with respect to reference genes (RGs). Ideally, RGs have a stable expression in different samples and are not affected by experimental conditions. The objective of this work was to analyze suitable RGs to study the role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…Besides, in the current study, b-actin has been used as the reference gene for RT-qPCR. Although it has been widely used for normalization in RT-qPCR, numerous studies suggested using multiple reference genes to achieve more convincing results with better stability (48)(49)(50). And this should also be considered in future validation studies.…”
mentioning
confidence: 99%
“…Besides, in the current study, b-actin has been used as the reference gene for RT-qPCR. Although it has been widely used for normalization in RT-qPCR, numerous studies suggested using multiple reference genes to achieve more convincing results with better stability (48)(49)(50). And this should also be considered in future validation studies.…”
mentioning
confidence: 99%